Institutional barriers to achieving good urban governance as a social determinant of health - Hossein Ayoubi Najaf Abadi; Navid Fatehi Rad; Sanjar Salajegheh; Mohammad Jalal Kamali (Shahid Beheshti University of Medical Sciences, 2021)
Background: Most of the factors that affect the community health are out of health sector. The aim of this study was to investigate institutional barriers to achieving good urban governance as a social determinant of health. Methods: The present study was a descriptive-correlational in terms of nature and survey in terms of method. The statistical population of the study included employees of Isfahan Municipality in Isfahan (n=15085). Based on Krejcie and Morgan table, the sample size was estimated at 376 people. They were selected using stratified random sampling method proportional to sample size. To collect data, researcher-made 41 items questionnaire was used on the barriers to achieve good urban governance. Cronbach's alpha coefficient was calculated as higher than 0.7. Data analysis was performed using structural equation modeling in AMOS-23 software. Results: The results showed that the effect of physical/spatial, social fragmentation and functional barriers on good urban governance was also significant. Also, the effect of barrier variables in the theoretical area of planning and management, functional barriers in the system of urban administration and management and political-planning barriers on good urban governance was significant. Negative path coefficients indicated that these structures had an inverse effect on good urban governance. Conclusion: A total number of six barriers were recognized that the government and municipalities can consider them in policy-making to achieve good urban governance and provide the conditions for development and expansion of cities according to urban standards This could be led to better situation in social determinants of health and higher level of health in community level.